2019
DOI: 10.1002/ptr.6291
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves the effect of a reduced insulin dose on glycemic control and oxidative stress in streptozotocin‐diabetic rats

Abstract: Insulin with natural antioxidants is emerging as a combination treatment for diabetes mellitus that attempts to exert effective glycemic control without adverse effects. The present study aimed to investigate the additive effects on metabolic disturbances, oxidative damage, and antioxidant defenses in streptozotocin-diabetic rats treated with curcumin and a reduced insulin dose. The best results were obtained in the treatment of diabetic rats with 4-U/day insulin; however, the glycemia levels in these rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…It must be highlighted that none of these curcumin doses caused toxicity in normal or diabetic rats. In further studies, when 90 mg/kg curcumin was administered in combination with carotenoids, lycopene or bixin [7], or with insulin [6], the effectiveness of curcumin was also observed in STZ-diabetic rats, and these combined treatments were able to add new benefits to combat the complications of diabetes associated with oxidative stress. In the present study, STZ-diabetic rats treated with curcumin-enriched yoghurt for 30 days showed maintenance of the glycemia values throughout the experimental period, in comparison with the progressive increase in the glycemia of DYOG rats, demonstrating the beneficial effects of curcumin on glycemic control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be highlighted that none of these curcumin doses caused toxicity in normal or diabetic rats. In further studies, when 90 mg/kg curcumin was administered in combination with carotenoids, lycopene or bixin [7], or with insulin [6], the effectiveness of curcumin was also observed in STZ-diabetic rats, and these combined treatments were able to add new benefits to combat the complications of diabetes associated with oxidative stress. In the present study, STZ-diabetic rats treated with curcumin-enriched yoghurt for 30 days showed maintenance of the glycemia values throughout the experimental period, in comparison with the progressive increase in the glycemia of DYOG rats, demonstrating the beneficial effects of curcumin on glycemic control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on diabetes, curcumin has gained attention due to its ability to ameliorate hyperglycemia and exert a range of beneficial effects on macro- and microvascular complications, including cardiovascular diseases [2], nephropathy [3], retinopathy [4], and endothelial dysfunction [5]. Furthermore, studies are showing promising findings on the efficacy of curcumin in combination with antidiabetic agents [6] or with other phytochemicals [7] in the control of glycemia and attenuating other diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that certain herbal extracts may prevent bone loss and protect against diabetes-induced bone microarchitecture disruption (21,22). Cur is an extract from the roots of the genus Curcuma and previous studies have revealed that it can reduce inflammation and oxidative stress in a diabetic rat model, improve islet cell function and reduce blood glucose levels (23,24). In addition, Cur may improve diabetes-induced damage of the retina, heart, kidney and other organs, thus demonstrating promising therapeutic effects against diabetic complications (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Wojcik et al, 2018;Gutierres et al, 2019;Den Hartogh et al, 2020 A Details of molecular targets mediated by curcumin (A) and important physico-chemical properties and their role in biological functions to remember when producing an effective nanoformulation of curcumin (B).…”
mentioning
confidence: 99%